Exploiting Space Syntax for Deployable Mobile Opportunistic Networking - Mtibaa, Abderrahmen; Harras, Khaled A. (IEEE International Conference on Mobile Ad-hoc and Sensor Systems, 2013)
Despite the plethora of opportunistic forwarding solutions offered by the research community, we revisit this domain from a new perspective by exploiting the concept of space syntax to enable deployable solutions in large scale urban environments. We present a set of algorithms that build upon space syntax, which predicts natural movement patterns by interacting with pre-built static environments. We design these algorithms for three assumption categories that represent the spectrum of assumptions regarding the underlying environment and node capabilities. We adopt a data-driven approach to evaluate the performance of our algorithms when compared to other state-of-the-art solutions within each representative category that make similar assumptions. Overall, our results show the great promise space syntax based algorithms have for efficiently guiding messages towards the destination. We show 5% to 20% success rate improvement compared to selected well known state-of-the-art forwarding algorithms within each assumption category while reducing the cost in terms of message replicas by up to 10%.